Tadalafil treatment for fetuses with early-onset growth restriction: a protocol for a multicentre, randomised, placebo-controlled, double-blind phase II trial (TADAFER IIb) - Hiroaki Tanaka; Yasuhiro Tanaka; Yoichi Aoki; Masayuki Endo; Tomoaki Ikeda; Shintaro Maki; Masafumi Nii; Kayo Tanaka; Satoshi Tamaru; Toru Ogura; Yuki Nishimura; Tomomi Kotani; et al. (BMJ Open)
Introduction TheTADAlafil treatment for Fetuses with early-onset growth Restriction: multicentrer, randomizsed, phase II trial (TADAFER II) study showed the possibility of prolonging the pregnancy period in cases of early-onset fetal growth restriction; however, it was an open-label study. To establish further evidence for the efficacy of tadalafil in this setting, we planned a multicentre, randomised, placebo-controlled, double-blind trial.Methods and analysis This trial will be conducted in 180 fetuses with fetal growth restriction enrolled from medical centres in Japan; their mothers will be randomised into three groups: arm A, receiving two times per day placebo; arm B, receiving one time per day 20 mg tadalafil and one time per day placebo and arm C, receiving 20 mg two times per day tadalafil. The primary endpoint is the prolongation of gestational age at birth, defined as days from the first day of the protocol-defined treatment to birth. To minimise bias in terms of fetal baseline conditions and timing of delivery, a fetal indication for delivery as in TADAFER II will be established in this trial. The investigator will evaluate fetal baseline conditions at enrolment and decide the timing of delivery based on this indication.Ethics and dissemination This study has been approved by Mie University Hospital Clinical Research Review Board on 22 July 2019 (S2018-007). Written informed consent will be obtained from all mothers before recruitment. Our findings will be widely disseminated through peer-reviewed publications.Trial registration jRCTs041190065.